A new usability testing model for business database transaction systems based on mccall' quality model - Siti Solehah, Othman; Noraziah, Ahmad; Roslina, Mohd Sidek (IEEE, 2025)
Usability testing is a critical evaluation process for systems, particularly those handling commercial database business transactions. This paper introduces a structured approach to usability testing tailored for such systems, emphasizing relevance, efficiency, user satisfaction, data integrity, transactional accuracy, and user interface dynamics. To support the usability framework, the initiated study integrates the application of theoretical assessment by conducting McCall’s Quality Model with the numeric assessment of actual usage. Subsequent t-tests, and analysis of variance (ANOVA) tests are performed to determine the probability of predominance between usability score outcomes, which serves as empirical verification of the proposed framework. Based on synthetic data and activity scenarios, this research performs comprehensive comparative experiments across various e-commerce platforms. A detailed analysis of a case establishes the integration of the levels of user experience and system requirements as well as the benefits and drawbacks of the suggested model. Effects established show that utilization of the proposed model provides modularity and versatility, alongside with high user satisfaction and system efficiency. This research benefits the field by translating the theory into empirical analysis to give a solid structure that can be applied in highly complex distributed database systems. Future development will concentrate on steps to advance this model and make it even more firm and adaptable.